Growth Rates and Relative Contributions of Different Components Towards the Productiun of Commercial Crops in Haryana - Lata, Swarn; Rawat, B S (Annals of Arid Zone, 2016)
An attempt has been made in the present paper to study the growth rates in area, production and productivity of oilseeds, sugarcane, potato and cotton in semi-arid regions of the Haryana State to measure the relative contributions of area, yield and rices in increase of crop production, decomposition analysis has been carried out The study is based on secondary data for 1966-67 to 1980-81. The results revealed that among all the commercial crops, only potato registered positive and significant growth rates in area. production and pruductivity in all the districts representing different zones. In case of oilseeds, growth rates in productivity were positive .for all the districts irrespective of negative area and production growth rates in some districts. Hisar observed highest positive growth rate in case of cotton. Growth rates in area as well as production revealed the association and conformity of the area with production for almost all the crops in all the three zones. A significante feature was observed from the decomposition analysis that the decrease in the contribution of area was associated with the increase in percentage share of price component. The analysis revealed that only a combination of increasing the per hectare- yield, more area under cultivation and better price would give positive growth impact.